1993
DOI: 10.1177/001440299305900408
|View full text |Cite
|
Sign up to set email alerts
|

“I've Counted Jon”: Transformational Experiences of Teachers Educating Students with Disabilities

Abstract: The purpose of this study was to describe the experiences of general education teachers who have had a student with severe disabilities in their class. Interviews of 19 general education teachers, kindergarten through Grade 9, as well as questionnaires completed by 18 teachers, were analyzed using categorical coding procedures to identify themes related to the teachers' experiences. Results showed that despite teachers' initial negative reactions to the placement of a child with severe disabilities in their cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(70 citation statements)
references
References 8 publications
6
60
0
4
Order By: Relevance
“…It is a logical result, teachers who had previously deal with students with Autism through their learning and training, or that they had received courses or training sessions in the field of Autism, or that they had a self-reading about Autism, it would be necessarily that they have a more advanced level of knowledge than those who do not did exposed to such experiences. This result was confirmed by (Giangreco et al, 1993) study indicating that direct experience in dealing with students with special needs is a critical factor in general educators' efficacy of teaching such a population and with their willingness to include such students in their class. Other studies also confirmed this results indirectly by stressing on the need for teachers to have more training course around how to deal with a student with Autism in an inclusive sittings (Stahmer et al 2005;Brownell et al 2003;Whaley, 2002).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is a logical result, teachers who had previously deal with students with Autism through their learning and training, or that they had received courses or training sessions in the field of Autism, or that they had a self-reading about Autism, it would be necessarily that they have a more advanced level of knowledge than those who do not did exposed to such experiences. This result was confirmed by (Giangreco et al, 1993) study indicating that direct experience in dealing with students with special needs is a critical factor in general educators' efficacy of teaching such a population and with their willingness to include such students in their class. Other studies also confirmed this results indirectly by stressing on the need for teachers to have more training course around how to deal with a student with Autism in an inclusive sittings (Stahmer et al 2005;Brownell et al 2003;Whaley, 2002).…”
Section: Discussionmentioning
confidence: 53%
“…Direct experience in dealing with students with special needs is a critical factor in general educators' efficacy of teaching such a population and with their ability to include such students in their class (Giangreco, Dennis, Cloniger, Edelman & Schattman, 1993). Specially, research indicates that general educators who teach children with disabilities do not have the capabilities necessary to meet the needs of these special learners (Campbell-Whatley, Obiakor & Algozzine, 1995).…”
mentioning
confidence: 99%
“…One theme has focused on the experience of inclusive classrooms for students with and without disabilities as well as their general and special education teachers (e.g., Giangreco, et al, 1993;Kozleski & Jackson, 1993). This theme also encompasses instructional processes such as peer assisted teaching and cooperative learning (e.g., Greenwood & Delquadri, 1995;McMaster, Fuchs, & Fuchs, 2006) and the ways in which special and general educators work together in the same classroom (e. g., Magiera, Smith, Zigmond, & Gebauer, 2006;Pugach & Johnson, 1995).…”
Section: Classroom Based Studies Of Inclusive Educationmentioning
confidence: 99%
“…Two studies published in 1993 explored the effects of placing students with severe disabilities into general education classrooms (Giangreco et al, 1993;Kozleski & Jackson, 1993). Socially and behaviorally, the students in each of these studies were able to participate in general education classrooms although they were described as having severe sensory and intellectual disabilities.…”
Section: Experiences In Inclusive Classroomsmentioning
confidence: 99%
“…Le degré d'inclusion de l'enfant dans une classe ordinaire ne représente donc qu'une facette de l'expérience scolaire de l'enfant et, comme l'ont montré d'autres auteurs (Giangreco et al, 1993 ;Green et Shinn, 1994, cités par Palmer et al, 1998, la satisfaction des parents envers l'école est davantage infl uencée par la présence d'un enseignant chaleureux qui prend soin de leur enfant que par le contenu des programmes. Les données de recherches empiriques (Palmer et al, 1997, cité dans Palmer, 1998 montrent que les parents d'enfants ayant des défi ciences intellectuelles sont plus enclins à avoir une perception positive de l'inclusion lorsqu'ils considèrent le développement d'habiletés sociales comme étant l'un des rôles importants de l'école.…”
Section: Les Facteurs De Réussiteunclassified